Variability in Susceptibility to Type I Interferon Response and Subgenomic RNA Accumulation Between Clinical Isolates of Dengue and Zika Virus From Oaxaca Mexico Correlate With Replication Efficiency in Human Cells and Disease Severity - Castro-Jiménez, Tannya Karen; Gómez-Legorreta, Laura Cristina; López-Campa, Laura Alejandra; Martínez-Torres, Valeria; Alvarado-Silva, Marcos; Posadas-Mondragón, Araceli; Díaz-Lima, Nallely; Angulo-Mendez, Hilda Arcelia; Mejía-Domínguez, Nancy R.; Vaca-Paniagua, Felipe; Ávila-Moreno, Federico; García-Cordero, Julio; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Dengue and Zika viruses co-circulate annually in endemic areas of Mexico, causing outbreaks of different magnitude and severity every year, suggesting a continuous selection of Flavivirus variants with variable phenotypes of transmissibility and virulence. To evaluate if Flavivirus variants with different phenotypes co-circulate during outbreaks, we isolated dengue and Zika viruses from blood samples of febrile patients from Oaxaca City during the 2016 and 2019 epidemic years. We compared their replication kinetics in human cells, susceptibility to type I interferon antiviral response, and the accumulation of subgenomic RNA on infected cells. We observed correlations between type I interferon susceptibility and subgenomic RNA accumulation, with high hematocrit percentage and thrombocytopenia. Our results suggest that Flaviviruses that co-circulate in Oaxaca, Mexico have variable sensitivity to the antiviral activity of type I interferons, and this phenotypic trait correlates with the severity of the disease.